Identificatión of paneth cells in the small intestione of alpacas in the first 21 days of age - Cueva M., Sergio (2012)
Paneth cells have an important function in the defense and protection mechanisms of the gastrointestinal tract in several animal species through secretions, e.g. as lysozime, secretory phospholipase A2 and defensins. The aim of this study was to identify the Paneth cells in the small intestine of baby alpacas. Eighteen culled animals between 1 and 21 days of age were used. Duodenum, jejunum and ileum samples were taken. Samples were fixed in 10% formalin, processed and stained with haematoxylin-eosin (H-E) and Masson trichromic. An anti-lizozime polyclonal antibody was used for immunohistochemistry. Typical Paneth cells were not identified with H-E and Masson trichromic stains, whereas lysozime granules were identified in the base of the crypts of Lieberkühn of duodenum, jejunum and ileum by immunohistochemistry since the first day of age. The number in jejunum and ileum was greater between 15 and 21 days of age. The cell area was between 129.19 and 147.67 μm2, major axes between 17.96 and 19.92 μm and minor axes between 8.68 and 9.79 μm. It is concluded that the observed cells corresponded to Paneth cells.